This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: } , either n is even or odd, and in either case  s ns  < . For the rest of the exercise, let s n = 11 2 + 1 3 + (1) n +1 1 n . (b) (5 pts) Prove that ( s 2 n ) is increasing and bounded above. Prove that ( s 2 n +1 ) is decreasing and bounded below. Solution: s 2( n +1)s 2 n = (1) 2 n +3 1 2 n + 2 +(1) 2 n +2 1 2 n + 1 =1 2 n + 2 + 1 2 n + 1 > so the subsequence is increasing. It is bounded above by 1 because s 2 n = 11 2 + 1 3 +(1) 2 n +1 1 2 n = 1 1 21 3  1 2 n21 2 n1 1 2 n , and all terms in the parentheses are positive. Proof that ( s 2 n +1 ) is decreasing and bounded below by 0 is similar. (c) (2 pts) Prove that lim s 2 n = lim s 2 n +1 . Conclude ( s n ) converges. Solution: lim s 2 n = lim s 2 n +11 2 n +1 = lim s 2 n +1 because lim 1 2 n +1 = 0....
View Full
Document
 Winter '11
 Wiley
 Differential Equations, Equations

Click to edit the document details